2022
DOI: 10.1002/pld3.422
|View full text |Cite
|
Sign up to set email alerts
|

A mutant allele of the flowering promoting factor 1 gene at the tomato BRACHYTIC locus reduces plant height with high quality fruit

Abstract: Reduced plant height due to shortened stems is beneficial for improving crop yield potential, better resilience to biotic/abiotic stresses, and rapid crop producer adoption of the agronomic and management practices. Breeding tomato plants with a reduced height, however, poses a particular challenge because this trait is often associated with a significant fruit size (weight) reduction. The tomato BRACHYTIC (BR) locus controls plant height. Genetic mapping and genome assembly revealed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Field trials of the inbred tomato set were conducted during three consecutive years, 2019, 2020, and 2021 at the UF Gulf Coast Research and Education Center (GCREC; Wimauma, FL, USA), where these tomatoes were originally bred, as described previously (‘Field trial’ section of Lee et al [ 6 ]). For the first, second, and third growing cycles, seed sowing in the greenhouse and fruit harvest were performed on August 5 and December 20, August 3 and December 23, and July 16 and December 2, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Field trials of the inbred tomato set were conducted during three consecutive years, 2019, 2020, and 2021 at the UF Gulf Coast Research and Education Center (GCREC; Wimauma, FL, USA), where these tomatoes were originally bred, as described previously (‘Field trial’ section of Lee et al [ 6 ]). For the first, second, and third growing cycles, seed sowing in the greenhouse and fruit harvest were performed on August 5 and December 20, August 3 and December 23, and July 16 and December 2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, the F 2 population set was grown in a field plot neighboring the inbred tomato set in 2020. For both the inbred tomato set and F 2 population set, fruit collection and yield (kg per plant) evaluations were performed, as described in our previous study (‘Field trial’ and ‘Greenhouse trial’ sections of Lee et al [ 6 ]). Briefly, all fruits with visually identifiable size (approximately > 0.5 cm in diameter) developed in each season were harvested on a single harvesting date, regardless of fruit size, quality (e.g., irrespective of whether the fruits had defects such as cracks), color, or flowering clusters bearing fruits; Fruits were sorted by size [ 3 ]; and by color into two classes, green ( G ; USDA color classification ‘Green’ [ 94 ]) and red ( R ; Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies also revealed that rice (Oryza sativa) and tomato (Solanum lycopersicum) homologs of FPF1 (known in rice as ACCELERATOR OF INTERNODE ELONGATION 1; ACE1) promote stem internode elongation but not flowering induction, suggesting that FPF1's function in tissue elongation is widely conserved among plant species, but it does not always accompany with acceleration of flowering. 17,18 Whereas the genetic pathway and interaction responsible for FPF1-dependent phenotypes are largely inconclusive, a recent study using Brachypodium distachyon revealed that FPF1 family proteins function as repressors of TFs through physical interaction. 19 In contrast to Arabidopsis FPF1, two FPF1 homologs of Brachypodium, FPL1 and FPL7, delay flowering.…”
Section: Introductionmentioning
confidence: 99%